2007
DOI: 10.1016/j.ejcts.2007.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Retransfusion of pericardial blood does not trigger systemic coagulation during cardiopulmonary bypass

Abstract: Objective: During cardiopulmonary bypass (CPB), systemic coagulation is believed to become activated by blood contact with the extracorporeal circuit and by retransfusion of pericardial blood. To which extent retransfusion activates systemic coagulation, however, is unknown. We investigated to which extent retransfusion of pericardial blood triggers systemic coagulation during CPB. Methods: Thirteen patients undergoing elective coronary artery bypass grafting surgery were included. Pericardial blood was retran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This is in line with a previous study in coronary artery bypass patients who underwent retransfusion of pericardial blood containing high levels of EVs. Although the vesicles isolated from pericardial blood increased thrombin generation in vitro, infusion of these vesicles did not have an in vivo effect on systemic coagulation . We feel that dilution of the infused vesicles following transfusion more closely resembles a relevant clinical situation than does measuring effects of a whole blood unit.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This is in line with a previous study in coronary artery bypass patients who underwent retransfusion of pericardial blood containing high levels of EVs. Although the vesicles isolated from pericardial blood increased thrombin generation in vitro, infusion of these vesicles did not have an in vivo effect on systemic coagulation . We feel that dilution of the infused vesicles following transfusion more closely resembles a relevant clinical situation than does measuring effects of a whole blood unit.…”
Section: Discussionmentioning
confidence: 88%
“…Another factor that may account for the differences are the use of autologous blood instead of allogeneic transfusion products. The studies that reported effects of transfusion products on coagulation parameters used allogeneic products, whereas studies that did not report an effect, including our own, used autologous products …”
Section: Discussionmentioning
confidence: 98%
“…Microvesicles released into the circulation have a half-life of a couple of minutes to a few hours [38], during which they may be taken up by neighboring or distant cells. In humans undergoing cardiopulmonary bypass, transfusion or dobutamine-induced cardiac stress, elevated levels of circulating microvesicles were detected, but these returned to baseline levels within 15 min to ~6 h [39, 40]. Interestingly, clearance of microvesicles may depend on the cellular origin of the microvesicles as platelet-derived microvesicles were cleared sooner than microvesicles released from red blood cells [40].…”
Section: Clearance and Uptake Of Extracellular Vesiclesmentioning
confidence: 99%
“…The study design has been detailed previously. 20 Briefly, thirteen patients who underwent elective coronary artery bypass grafting assisted by CPB were included prospectively. Inclusion criteria were body surface area >1.66 m 2 and preoperative hemoglobin levels >7.5 mmol/L.…”
Section: Methodsmentioning
confidence: 99%
“…Two of the patients who were retransfused with pericardial blood also received allogeneic blood products (red cell concentrates). For a description of the extracorporeal system and the surgical procedure see the manuscript of van den Goor et al 20 This study was approved by the ethical committee of the Academic Medical Center of the University of Amsterdam and complies with the principles of the Declaration of Helsinki. All patients had given their written informed consent.…”
Section: Methodsmentioning
confidence: 99%